Analisis Faktor-Faktor yang Memengaruhi Komitmen Personal dalam Pelaksanaan CSR di Pabrik Semen PT SBA Aceh Besar - Wiki Noviandi; Agusmadi Agusmadi; Azlim Azlim (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Industrial development, especially the cement sector, contributes significantly to economic progress, but also poses environmental challenges. This study aims to analyze the influence of collaboration management and leadership on employee personal commitment at the PT SBA Aceh Besar Cement Factory. The research method used was a survey with a questionnaire distributed to 127 respondents. The results of the analysis showed that collaboration management had a significant influence on personal commitment, while leadership did not show a significant influence. This finding emphasizes the importance of collaboration management in increasing employee commitment, which in turn can support operational sustainability and corporate social responsibility. This study recommends increasing collaboration training and developing leadership styles that support collaboration to increase employee personal commitment.